An investigation on structural, morphological, optical and third order nonlinear properties of facilely spray pyrolysis fabricated In:CdS thin films. (September 2019) - Shkir, Mohd; Anis, Mohd; Shaikh, S.S.; AlFaify, S.
Abstract: Owing to the tremendous applications of cadmium sulphide (CdS), the fabrication of different content of In doped (0.0, 0.5, 1.0, 2.5 and 5.0 wt%) CdS thin films has been carried out facilely by spray pyrolysis technique. X-ray diffraction and FT-Raman studies confirm the single phase of CdS with hexagonal crystal system. The Scherrer rule was employed to determine the crystallite size and found to be reduced from 20 to 18 nm. The elemental composition and mapping studies shows that the prepared films contain In in CdS which is homogeneously distributed all over the film. The surface morphology was studied and noticed to be modified with increasing the content of In doping. The emission spectra were recorded at λexc  = 450 nm and an intense green emission was observed at 529 ± 16 nm for pure and In:CdS films. The optical study reveal that the optical transparency is enhanced from 65% to 75% with In doping. The refractive index was noticed in range from 1 to 2.8. The direct optical energy gap was estimated in the range from 2.31 to 2.46 eV and shows reduction with In content. The open and closed aperture Z-scan measurement was carried out and nonlinear absorption, third order nonlinear susceptibility and refractive index values were determined and found in range from 3.12 × 10 −3 to 5.37 × 10 −3  cm/W, 4.67 × 10 −1 to 7.01 × 10 −1  esu and 2.14 × 10 −7 to 5.99 × 10 −7  cm 2 /W, correspondingly. Graphical abstract: Image 1 Highlights: Facile fabrication of In:CdS thin films was carried out by spray pyrolysis technique. Polycrystalline nature of hexagonal phase CdS films was approved by structural and vibrational studies. The elemental mapping and EDX spectra confirm homogeneous doping of In in CdS films. SEM micrographs confirms low dimension grains formation in all In:CdS films. The χ 3 and n 2 values are estimated in range of 4.67 × 10 −1 to 7.01 × 10 −1  esu and 2.14 × 10 −7 to 5.99 × 10 −7 cm 2 /W from Z-scan study.